PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) BERBASIS ANDROID TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN RUANG - Husnaidi Husnaidi (LPPM Universitas Bina Bangsa, 2023)
This research is motivated by the lack of technology-based learning media and the low academic performance of students. The aim of this research is to determine the extent of the influence of learning media on students' academic performance. This research employs a quantitative approach with a descriptive survey method, involving all VA class students as the sample, totaling 30 respondents. Statistical tests used include validity test, reliability test, normality test, simple linear regression test, F-test, t-test, and coefficient of determination (R2). The research results indicate that there is a significant and positive influence collectively (simultaneously) between the learning media (X) and student interest (Y), with an F-value of 54.529, which is greater than the F-table value of 4.20, at a significance level of 0.001. Furthermore, the coefficient of determination (R2) test shows that the learning media (X) has an influence of 66.1% on students' learning outcomes (Y). Therefore, based on the results, it can be concluded that there is a significant influence of using Augmented Reality as a learning media on students' learning outcomes, with the null hypothesis (Ho) rejected and the alternative hypothesis (Ha) accepted